Prospects and strategies for accelerating the growth of the agriculture and allied sector in Odisha with specific reference to dairying - Dilip Rath,; Yogesh C Joshi, (Agricultural Economics Research Review, 2023)
Odisha is endowed with rich natural resources and a diverse agroclimatic zone. All these provide sufficient potential to boost its agricultural sector. However, the average monthly income of an agricultural household in Odisha from farming was merely INR 1,407 per month, out of a total income of INR 4,976 per month from all sources, the second lowest in the country as per the 70th round survey (2012–13) of the National Sample Survey Office. Dairying can accelerate income growth in Odisha, and this paper explores its various facets. The discussion can help policymakers design and implement dairy development programmes.